1992
DOI: 10.1136/bmj.304.6831.873
|View full text |Cite|
|
Sign up to set email alerts
|

Respiratory symptoms and atopy in Aberdeen schoolchildren: evidence from two surveys 25 years apart.

Abstract: Objective-To estimate changes in the prevalence of respiratory symptoms and the reported diagnoses of asthma, eczema, and hay fever in primary school children in Aberdeen between 1964 and 1989.Design-Determination of incidence prevalence and prevalence from survey data.Setting-Aberdeen, Scotland. Participants-2743 primary school children (aged 8-13) from 1964 and 3942 from 1989.Main outcome measures -Survey data on whether, according to the parent or guardian, the child wheezed or was troubled with shortness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
299
9
17

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 605 publications
(349 citation statements)
references
References 17 publications
(7 reference statements)
23
299
9
17
Order By: Relevance
“…The rates of increase are substantial and equivalent to a y5% increase per annum in the number of subjects affected, but they are similar to those reported in other studies in which the same population has undergone repeated investigation [1][2][3][4][5]. The rates of increase are more striking in subjects aged v30 yrs.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The rates of increase are substantial and equivalent to a y5% increase per annum in the number of subjects affected, but they are similar to those reported in other studies in which the same population has undergone repeated investigation [1][2][3][4][5]. The rates of increase are more striking in subjects aged v30 yrs.…”
Section: Discussionsupporting
confidence: 75%
“…An increase in disease prevalence has been supported by a number of studies in which the same population has been surveyed more than once at intervals of ¡25 yrs [1][2][3][4]. Observed rates of change for those affected within UK populations have been w6% per annum for 8-13-yr-old children [1,2], 7% per annum for university entrants [3], and 8% per annum for 12-yr-old children [4]. These findings were based on questionnaire responses, and so may have been influenced by increased awareness of asthmatic symptoms and an increased likelihood of reporting them.…”
mentioning
confidence: 95%
“…BRABÄCK et al [15], in a comparison of atopic sensitization and respiratory symptoms among Swedish and Polish school children, reported that children living in urban Sweden, as compared to urban Poland, were more frequently diagnosed as being asthmatic by a doctor, and had higher prevalences of positive skin-prick test reactions against mugwort, timothy, birch and cat. Several studies have indicated a rising trend in atopic diseases and asthma over time both in children [16][17][18][19][20][21] and adolescents [2,22,23]. Most authors suggest that this is not simply due to improved diagnostic trends.…”
Section: Discussionmentioning
confidence: 99%
“…(2,3) Genetic factors, although important, probably do not explain that increase, which has been attributed to the interaction between genetic and environmental factors. Environmental factors seem to have greater relevance in the determination of the symptoms of asthma, (4,5) the etiology of which remains poorly understood, despite a considerable amount of research in the area.…”
Section: Introductionmentioning
confidence: 99%
“…(6,19) The questionnaires were completed by the students themselves, in the classroom and in the presence of the principal researcher or one the research assistants, duly trained by the formerthey received a manual developed by the ISAAC Fortaleza is located on a coastal flat, immediately below the equator, between latitude 3°30' and latitude 4°30', at an altitude of 15.49 m above sea level. It has an area of 4,667.8 km 2 and had a population of 2,431,415 inhabitants in 2000. (14) The annual mean temperature ranges from 26 to 27°C, and the relative humidity is approximately 82%.…”
Section: Introductionmentioning
confidence: 99%